The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1111/cbdd.13837
|View full text |Cite
|
Sign up to set email alerts
|

Toll‐like receptor 4 antagonist FP7 alleviates lipopolysaccharide‐induced septic shock via NF‐kB signaling pathway

Abstract: Septic shock is the most severe complication of sepsis occurs when body has an overwhelming response to infection, making it the most prevalent cause of deaths in surgical intensive‐care units. Therefore, it is urgent to understand its pathogenesis and develop new therapeutic candidate drugs for septic shock. Here, we explored the effect of FP7, an antagonist of Toll‐like receptor 4 (TLR4), in the septic shock. First, we injected mice with FP7 and found that FP7 had no effect on immune cells. Then, bone marrow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Studies have shown that both vitexin and donepezil are able to bind in close proximity to the LPS binding site located on the TLR4-MD-2 complex, which has the potential to be a candidate antagonist for LPS [ 130 ]. TLR4 antagonist treatment significantly increases survival, ameliorates lung necrosis, and inhibits inflammatory cytokine secretion in septic shock mice [ 131 ]. These studies point to the promise of the therapeutic effects of LPS antagonists in the treatment of sepsis.…”
Section: Treatments For Lps-induced Sepsismentioning
confidence: 99%
“…Studies have shown that both vitexin and donepezil are able to bind in close proximity to the LPS binding site located on the TLR4-MD-2 complex, which has the potential to be a candidate antagonist for LPS [ 130 ]. TLR4 antagonist treatment significantly increases survival, ameliorates lung necrosis, and inhibits inflammatory cytokine secretion in septic shock mice [ 131 ]. These studies point to the promise of the therapeutic effects of LPS antagonists in the treatment of sepsis.…”
Section: Treatments For Lps-induced Sepsismentioning
confidence: 99%
“…NF-κB represents a therapeutic target since it induces pro-inflammatory gene transcription implicated in the septic shock[ 71 ]. In fact, in LPS-induced septic shock murine models, NF-κB inhibitors such as parthenolide and pyrrolidine dithiocarbamate[ 71 ], or an antagonist of toll-like receptor 4, the FP7[ 72 ] reverse sepsis effects on organ failure and hypotension. G protein-coupled receptors (GPCRs) may be potential targets for pharmacotherapy in sepsis.…”
Section: Orexins and Septic Shockmentioning
confidence: 99%